The overcoat and other short stories - Gogol, Nikolai (Constable, 1992)
Four works by great 19th-century Russian author: "The Nose," a savage satire of Russia’s incompetent bureaucrats and its snobbish and complacent upper classes; "Old-Fashioned Farmers," a pleasant depiction of an elderly couple living in rustic seclusion; "The Tale of How Ivan Ivanovich Quarrelled with Ivan Nikiforovich," one of Gogol’s most famous comic stories; and "The Overcoat," widely considered a masterpiece of form.